Mob psycho 100. Reigen : the man with level 131 max spirit power! - ONE, 1986- (Dark Horse Manga, 2020)
"In a world haunted by dangerous supernatural forces, there are still some problems you can't solve no matter how much spiritual power you have. And a good thing too--because phony exorcist Reigen Arataka doesn't have any! But that's never stopped Reigen from running a ghostbusting business... and his new part-time office assistant is none other than Tome Kurata, a girl obsesssed with the strange and unxplained--and the schoolmate of Reigen's protege, Shigeo Mob Kageyama. Yet whereas Mob's incredible psychic strength resolved many a case for Reigen, Tome is as powerless as her boss! Or so she may think at first... but if there's one thing a master scam artist knows how to teach, it's the power of confidence and belief!"--Provided by publisher.